(untitled) (Africa Development, 1980)
CONTENTS A New Dimension in International Development Assistance: The Role of the Organisation of Petroleum Exporting Countries (OPEC) F. AKIN OLALOKU ....................... 6 Sous-Développement de l'Agriculture et Pauvreté d'un Pays Riche : Cas du Zaire KANKUENDA M'BAYA ..................... 24 Some Thought on the «Trust» System in Eastern Nigeria O. N. NJOKU .......................... 37 Soins de Santé Primaire et Médecine Traditionnelle — A propos du Développement des Concepts de Santé Publique en Afrique Dr. BICHMANN WOLFGANG ................... 50 Economie Integration in West Africa: Some Critical Issues S. K. B. ASANTE .............................. 67 REVIEWS Unequal Exchange, Imperialism and Underdevelopment: An Essay on the Political Economy of Imperialism, (Oxford University Press, Calcutta, 1978), by Ranjit SAU THANDIKA MKANDAWIRE .............................. 84